Tswana-speaking students’ perceptions of HIV/AIDS and poverty - Paul Schutte (Communicare)
This article addresses the perceptions of the causal relationship between poverty and HIV/AIDS among selected Tswana-speaking students by using the theoretical framework of one of the theories of symbolic interactionism, also known as the Fantasy Theme Analysis or Symbolic Convergence theory. This theory is designed to provide insights into the shared world views of communicators, which would result in a better understanding of a rhetorical situation. This understanding will enable communication agents to articulate more audience-centred messages in their combat against HIV/AIDS. This article describes the theoretical framework and research method that have been used. After the synthesis of the findings, recommendations are made with regard to communication with this specific target audience, but suggestions are also given to address any target audience. The research indicates that there are two shared rhetorical visions exist. Almost 74% of the respondents shared the vision that poverty is the cause of AIDS, although most of them mentioned that unprotected sex with multiple partners plays a major role. The other vision, shared by 26% of the respondents, perceives unprotected intercourse with several partners, and not poverty, to be the cause. The lack of values and morals as well as uncontrolled sexual drives are perceived as contributing factors.